Maturation to elite status: a six-year physiological case study of a world champion rowing crew - Mikulic, P. (European Journal of Applied Physiology, 2011)
This case study reports the results of a 6-year (2005-2010) follow-up study of a world-class rowing crew, the current world champions. The rowers were 15-16 years old and prospective competitors at the junior level when the study began in 2005, and we monitored their physical, physiological, and rowing ergometer performance data annually. Our findings indicated that over the 6-year period gains in stature, averaged across rowers, amounted to only +2 cm (+1%). In contrast, body mass increased by +9 kg (+10%) and fat-free mass by +11 kg (+15%). A significant linear trend (R 2 = 0.998, P < 0.001) and a +26% increase in maximal oxygen uptake (in L/min) was evident from 2005 to 2009, resulting in a leveling-off and a crew average of ~6.6 L min-1 (~70 mL/kg/min) during the last 2 years of assessment. Power output at anaerobic threshold increased by +23%, subsequently amounting to a crew average of 359 W in 2010. Oxygen uptake at anaerobic threshold, expressed as a percentage of maximal oxygen uptake, changed little and ranged between 82 and 85%. A curvilinear regression provided the best fit to describe the 6-year improvement (+7%) in 2000 m (R 2 = 0.984, P < 0.001) and 6000 m (R 2 = 0.989, P < 0.001) rowing ergometer performance times. Performance-related physical and physiological parameters seem to level-off at about 20 years of age, which may partly explain the corresponding stabilization in ergometer performance times over the last years of assessment.